Pengembangan Kurikulum Bahasa Arab dalam Meningkatkan Kemampuan Pemahaman Al-Quran di Lembaga Pendidikan Islam - Zakiyah, Zakiyah; Karimah, Safa’atul; Fakhriyah, Sani; Jauharoh, Titin; Putri, Arum Kusmila Surya (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2024)
Islamic education views understanding the Al-Quran as the main foundation in forming the religious identity and morality of Muslim individuals. The Arabic language curriculum in Islamic educational institutions is a key tool in guiding students to absorb and understand the holy messages of the Al-Quran. This research was conducted to develop an effective Arabic language curriculum to improve understanding of the Al-Quran in Islamic educational institutions. Literature reviews, interviews with Islamic education experts, and evaluations of existing Arabic curricula reveal shortcomings in facilitating in-depth understanding of the Qur'an. The proposed curriculum emphasizes a contextual approach by integrating Al-Qur'an exegesis (tafsir) and historical context. This aims to ensure that students not only understand the text literally but also gain a deeper understanding of the meaning and message contained in it. Furthermore, the curriculum emphasizes the development of Arabic language skills to facilitate understanding and interaction with the Al-Quran. This includes understanding grammar, vocabulary, and the ability to apply Arabic language structures in reading and understanding the Al-Quran text. The importance of considering students varying levels of ability was also highlighted in the development of this curriculum. By accommodating different skill levels, the curriculum can be tailored to ensure that each student can gain maximum benefit from learning. Through the development of a more contextual and skills-oriented curriculum, it is hoped that the overall quality of Islamic education will improve. In addition, this curriculum is expected to strengthen students religious identity and increase their understanding of the Al-Quran, thereby having a positive impact on the Muslim community at large.